Estabilidade e manejo integrado visando ao controle de ferrugem asiática por meio do emprego de multilinhas - Vilela, Nelson Júnior Dias (2019)
Soy is the main product of Brazilian agribusiness. However, the culture is highly influenced by environmental factors such as management and predictable and unpredictable environmental factors. Thus, research was carried out in this work with the intention of increasing the knowledge of the soybean crop. The first work aimed to compare the performance of INOX® soybean genotypes with and without application of fungicide to agronomic characters, as well as to quantify the efficiency of the use of multilines in soybean crop aiming at controlling Asian rust. Two different experiments were conducted, one in a greenhouse and another in the field. In the first experiment six commercial soybean cultivars were evaluated (TMG 7060 IPRO, TMG 7063 IPRO, TMG 7262 RR, TMG 7062 IPRO, TMG 7363 RR, TMG 7067 IPRO) and also a multiline (mixture of strains). The evaluated environments were Lavras and Ijaci in the 2017/18 crop, and Lavras, Ijaci, Itutinga and Inconfidentes in the 2018/19 crop. A randomized complete block design was used, and the treatments were divided into plots subdivided into strips, 4 x 7 (4 managements of fungicide applications and 6 cultivars + one multiline), with three replications, being the number of applications in the plots and the cultivars in the subplots. The increasing number of foliar fungicide applications improves on grain yield and absolute maturity. The cultivar TMG 7067 IPRO presented higher average grain yield and absolute maturity. In addition to the genotypes used in the field experiment, a susceptible cultivar was added to the second experiment conducted in a greenhouse. Plants were inoculated with P. pachyrhizi uredospores. The statistical design used was a randomized complete block with four replications, each repetition consisting of four pots with three plants per pot. There is no difference for the evaluated characters between the cultivars per se and the multiline. Multiline cultivar INOX® is effective in reducing the severity of Asian rust in soybeans. The second work aimed to study the adaptability and stability of soybean genotypes in different environments as well as the identification of cultivars that contribute less to the G x E interaction for growing conditions in southern Minas Gerais. Six commercial soybean cultivars and one multiline were evaluated. The evaluated sites were in Lavras and Ijaci in the 2017/18 and 2018/2019 crops, and Itutinga and Inconfidentes in the 2018/2019 crop, and four experiments were installed in each location, totaling twenty-four environments. The experimental design was a randomized complete block design with three replications in a factorial scheme. The mixture of strains is an efficient strategy to increase the phenotypic stability in soybean. The multiline and cultivar TMG 7063 IPRO have broad stability and adaptability. The cultivar TMG 7067 IPRO presents the highest confidence index with great contribution to the interaction.